2016
DOI: 10.1002/pssa.201532748
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature optical response of zinc oxide nanowires synthesized by chemical bath deposition to toluene vapors

Abstract: International audienceZinc oxide (ZnO) nanowires were synthesized by a simple and cost-effective process, namely chemical bath deposition. X-ray diffraction (XRD) pattern clearly shows that the nanowires are well crystallized in the wurtzite hexagonal structure. Field-emission scanning electron microscope (FESEM) images show the formation of perfectly aligned and organized nanowires, with no defects visible on their surface. The diameter and length of nanowires is 65 and 850 nm, respectively. The room temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In order to synthesize such monodisperse metal oxide nanowires, most fundamental research has been devoted to understand the principles of nanowire growth using various techniques, including vapor-phase and solution-phase synthesis. Many studies consistently showed the crucial importance of a homogeneously sized initial nucleation to obtain the monodisperse nanowires. For controlling the initial nucleation, a seed prepatterning approach on substrate that defines the seed size has been demonstrated via different lithographic techniques. ,, However, these techniques are very costly and restricted to operation in limited areas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to synthesize such monodisperse metal oxide nanowires, most fundamental research has been devoted to understand the principles of nanowire growth using various techniques, including vapor-phase and solution-phase synthesis. Many studies consistently showed the crucial importance of a homogeneously sized initial nucleation to obtain the monodisperse nanowires. For controlling the initial nucleation, a seed prepatterning approach on substrate that defines the seed size has been demonstrated via different lithographic techniques. ,, However, these techniques are very costly and restricted to operation in limited areas.…”
Section: Resultsmentioning
confidence: 99%
“…We serendipitously found the emergence of monodisperse ZnO nanowires from randomly sized seeds when hydrothermal synthesis , was conducted by a two-step process composed of an ammonia-added “step 1” and an ammonia-free “step 2”. Figure a,b shows typical field emission scanning electron microscopy (FESEM) images of ZnO nanowires fabricated by two-step and single-step growth, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The authors report herein various material synthesis aspects like zirconia coatings fabricated by aerosol‐gel routine, enhanced with low temperature plasma discharge , 65 nm‐thick ZnO nanowires grown by a cost‐effective process called chemical bath deposition or ALD growth of electrically efficient ZnO/4H‐SiC n‐p heterojunction diodes .…”
mentioning
confidence: 99%